A rare pediatric case of a thymic cytotoxic and lymphoblastic T/NK cell lymphoma - Gaiser, Timo; Haedicke, Wolfgang; Gaiser, Maria (International journal of clinical and experimental pathology, 2010)
Attempts to establish a concise classification of lymphoblastic lymphomas (LBLs) have gained momentum in recent years, mainly due to the expanding possibilities of immunohistochemical and genetic characterization of different disease entities. Thus, cases ...
Gesehen am 21.11.2023